Variant of Hoffa disease: a case report - Sharifah Nor Amirah Syed Abdul Latiff Alsagoff; Mohd Fairudz Mohd Miswan; Mohd Yusoff Yahaya; Mohamed Faizal Sikkandar; Anis Safura Ramli (Malaysian Family Physician, 2025)
This report presents the case of an 18-year-old female student with a low BMI, who was otherwise healthy. She presented with chronic anterior right knee pain persisting for 1 year. The pain began spontaneously and gradually increased in severity, especially during long distance walking and standing for more than 15 minutes. The symptoms did not subside with medication and physiotherapy. All biochemical and radiological investigations to rule out other related possible aetiologies were unremarkable. The patient eventually underwent an arthroscopic knee surgery, during which the intraoperative findings revealed the Hoffa fat pad over the anteromedial knee joint. This was debrided and after surgery, she was symptom free and had resumed her normal activities.